Additional energy supplements in the diet for fattening rabbits - Yamani K.A.O.; Ayyat M.S.; Bassuny S.M.; Rashwan A.A.; Abdalla M.A. (Rabbit production in hot climates, 1994)
A total of 32 weaned New Zealand White (NZW) male rabbits (7 weeks of age) were divided into 4 groups (8 each) to be used in a study aimed at utilizing the animal and vegetable fats (tallow and palm oil) and starch in pelleted diets as additional energy source in feeding growing rabbits compared with the basal diet (without additional energy source) in Egypt. Results obtained indicated that supplementation of growing rabbit grower diets with tallow improved significantly (P less than 0.05) the EE digestibility, final body weight at marketing age (13 weeks), daily weight gain, serum total lipids and serum cholesterol compared to the other groups. Carcass traits and chemical composition of meat did not differ significantly among the studied groups. However, the grower diet group was of less feed intake and of lower feed cost and gave the best economical efficiency percentage. The return from the improved performance by the additional tallow did not compensate for the expensive diet. The results rejected the additional energy resources to the grower diet and concluded that 2500 kcal DE pelleted diet is adequate for growth and carcass performance in rabbits.
1. International Conference of rabbit production in hot climates, 1994/09/06-08, Cairo (Egypt)